Multi-access mixed cognitive body area network architecture. (1st January 2014) - Zhang, Chijun; Sun, Tiezheng; Du, Zhanwei; Han, Jialing
A novel multi-access mixed cognitive body area network architecture is proposed by us, based on theories of cognitive networks, situational awareness, wireless communication infrastructure and topology control technology, to research this layered scalable wireless BAN cognitive model of wireless network architecture. Through the analysis of wireless body area network, a novel cognitive model and the cross-layer model are introduced. The balance between communication and efficient data transmission is met from the perspectives of security, reliability, and so on. Besides, this paper also explores the architecture theory of low radiation and the 'green' communications to some extent.